2020
DOI: 10.1021/acsnano.0c01436
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Flap-Type Difunctional Sensor for Detecting Pneumatic Flow and Liquid Level Based on Triboelectric Nanogenerator

Abstract: In recent years, the triboelectric nanogenerator (TENG) has attracted increasing attention because it not only converts various mechanical energy into electrical energy but also produces electrical signals as responses. On the basis of the TENG, a magnetic flap type difunctional sensor (MFTDS) has been developed to detect pneumatic flow and liquid level. Consisting of an outer magnetic flap, an inner magnetic float, and a conical cavity, its working mechanism and output characteristics were studied. The MFTDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 38 publications
(45 reference statements)
0
36
0
Order By: Relevance
“…Copyrightª2018, Wiley-VCH. Reproduced with permission (Wang et al, 2020b). Copyrightª2018, American Chemical Society.…”
Section: Teng-based Multifunctional Self-powered Sensors Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyrightª2018, Wiley-VCH. Reproduced with permission (Wang et al, 2020b). Copyrightª2018, American Chemical Society.…”
Section: Teng-based Multifunctional Self-powered Sensors Principlesmentioning
confidence: 99%
“…The production of daily chemical products, marine engineering construction, and early warning of marine disasters cannot be separated from the monitoring of liquid level (Shao et al, 2020;Fu et al, 2020). For promoting the application of TENG in SPMS, Wang et al designed a magnetic flap-type multifunctional sensor system based on the triboelectric effect, which can be used to detect pneumatic flow and liquid level (Wang et al, 2020b). The main components of the sensor system include a magnetic float that can be moved up and down by applying force and therefore create a moving magnetic field, a magnetic flap of which half of the surface is covered by copper electrodes with half-cylinder shape that can rotate 180 by the direction of the external magnetic field, as exhibited in Figure 6A.…”
Section: Other Sensors Based On Tengmentioning
confidence: 99%
“…The triboelectric nanogenerator (TENG, also called the Wang generator [16]), first proposed by Wang Group in 2012, provided a new approach of converting mechanical energy into electricity [17][18][19]. The output signal of TENGs can well reflect the change of mechanical excitation, and TENG has good adaptability to various forms of mechanical motion, thus it is considered to be the potential solution of self-powered sensing [20][21][22][23][24]. In recent years, researchers have realized a preliminary exploration of rotation sensing Sensors 2021, 21, 1713 2 of 11 and monitoring [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have demonstrated that TENG has advantages of wide material applicability, simple structure, small size, low cost, and high integration. [ 20–22 ] Meanwhile, Zhang et al. conducted in‐depth study on improving the electrical output capacity of TENG.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have demonstrated that TENG has advantages of wide material applicability, simple structure, small size, low cost, and high integration. [20][21][22] Meanwhile, Zhang et al conducted in-depth study on improving the electrical output capacity of TENG. [23,24] Recently, many triboelectric mechanical motion sensors with a sliding freestanding triboelectric layer have been proposed for different detection objects, including linear motion sensors, [10,25] rotational motion sensors, [26,27] and angular motion sensors.…”
mentioning
confidence: 99%